Carbon-storing artificial stone / block
The carbon storage artificial stone/block addresses the limitations of existing carbon storage materials by combining dredged soil, steelmaking slag, and a carbon compound to achieve stable carbon storage and high strength, suitable for diverse applications including underwater structures, while reducing emissions.
Patent Information
- Application Number
- JP2024088669
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-07
- Filing Date
- 2024-05-31
- Publication Date
- 2025-01-21
AI Technical Summary
Existing carbon storage materials, such as carbon-storing mixed materials and calcia artificial stones, have low mechanical strength and limited applications, primarily suitable for ground materials like backfilling and revetment, and do not effectively store carbon in water areas due to low carbon fixation and high emissions from cement use.
A carbon storage artificial stone/block is created by mixing dredged soil with steelmaking slag, a binder, and a carbon compound containing at least 10% carbon by mass, which stabilizes carbon storage and achieves a strength of at least 1.0N/mm after 28 days, using inorganic and organic compounds to enhance durability and strength.
The carbon storage artificial stone/block effectively stores carbon over a long period while maintaining high mechanical strength, suitable for various applications including rubble, covering stones, and underwater structures, reducing emissions by utilizing steelmaking slag to fix carbon dioxide as calcium carbonate.
Smart Images

Figure 2025010493000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a carbon storage artificial stone block made of dredged soil, steel slag, a binder, and a carbon compound. [Background technology]
[0002] As part of measures against global warming, biochar is being applied to agricultural land to store carbon by fixing persistent carbon in the soil for a long period of time. Biochar is said to be effective in improving soil permeability, water retention, and breathability, and has been used as a soil improvement material for some time. It can also reduce greenhouse gases and contribute to climate change measures (see Non-Patent Document 1). Biochar is a carbonized material made from biological resources that is effective in activating organisms and improving the environment. It is a solid material made by heating biomass at a temperature of over 350°C under oxygen concentrations controlled to a level that does not cause combustion.
[0003] Research is being conducted on the carbon storage effect of utilizing the organic carbon in dredged soil generated during dredging work, but in terms of storage effect, the organic carbon derived from dredged soil is about 1.3%, which is not much compared to biochar (carbon content 77%) (see non-patent document 2).
[0004] Calcia-modified soil is a solidification-treated soil in which steelmaking slag is mixed with soft dredged soil to increase its strength (see Patent Document 1, etc.). The present inventors previously proposed in Patent Application No. 2023-24865 a carbon storage mixed material that stores more carbon stably for a long period of time by adding carbon-containing materials such as biochar when mixing the calcia-modified soil and solidifying it.
[0005] Environmentally friendly concrete is known in which biochar such as woody biomass is mixed in and solidified to store carbon and reduce CO2 emissions (see Non-Patent Document 3). High-fluidity concrete is also known in which a large amount of calcium carbonate fine powder that fixes CO2 captured from exhaust gas is mixed in to reduce CO2 emissions (see Non-Patent Document 4).
[0006] Also, calcia artificial stone blocks are known that are manufactured by mixing steelmaking slag, ground granulated blast furnace slag, and the like with dredged soil (see Patent Document 2 and Non-Patent Document 7). Calcia artificial stone aims to recycle steelmaking slag and dredged soil, and is a substitute for natural stone, so it contributes to reducing the amount of natural resources input in port construction. Patent Document 3 discloses a ground material that contains at least one of cement, ground granulated blast furnace slag, fly ash, silica fume, rice husk ash, and the like in addition to soft soil and granular materials such as steelmaking slag (paragraph 0047).
[0007] Regarding the design standard strength of calcia artificial stone blocks, for example, Non-Patent Document 7 states that the design standard strength of calcia artificial stone is 9.8N / mm for semi-hard stone equivalent. 2 The soft stone equivalent is 3 to 9.8N / mm 2 For calcia blocks, the strength is 18N / mm for irregular blocks and cubic blocks. 2 Above, 9.8N / mm 2 The above is stipulated. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2009-121167 A [Patent Document 2] JP 2012-148948 A [Patent Document 3] JP 2018-184823 A [Non-patent literature]
[0009] [Non-Patent Document 1] "About Biochar" (Ministry of Agriculture, Forestry and Fisheries) https: / / www.maff.go.jp / j / kanbo / kankyo / seisaku / climate / jcredit / biochar / biochar.html [Non-Patent Document 2] Ryoji Naito, Yoshiyuki Nakamura, Taro Urase, and Naohiro Kaneko, "Relationship between the concentration of chemical substances in bottom sediments and the benthic biota in harbor areas," Journal of Environmental Engineering Research, vol. 44, pp. 7-16, 2007. https: / / www.jstage.jst.go.jp / article / proes1992 / 44 / 0 / 44_0_7 / _pdf / -char / ja [Non-Patent Document 3] Ryota Kihara, Keiji Koda, Shinya Yamamoto, Kazuaki Shimizu, Hirokazu Tanaka, and Masashi Kubo, "Hardening properties of environmentally friendly concrete containing biochar," JSCE 77th Annual Academic Lecture, National Conference of the Japan Society of Civil Engineers, 2022, V-245, 2022https: / / jglobal.jst.go.jp / detail?JGLOBAL_ID=202302248682592714 [Non-Patent Document 4] Noboru Sakata, Goro Sakai, and Kenzo Watanabe, "CO2 reduction by applying high-fluidity concrete containing a large amount of calcium carbonate fine powder," JSCE 77th Annual Academic Lecture, National Convention of the Japan Society of Civil Engineers, 2022, V-518, 2022 [Non-Patent Document 5] T. Tsuji, Y. Tanaka, M. Nakagawa, S. Nonaka, K. Nagao, Y. Akashi, H. Kiso, and C. Tasaki, "Material properties and manufacturing technology of artificial stone made from dredged soil," Journal of the Japan Society of Civil Engineers, B3, vol. 71, pp. 1173-1178, 2015. https: / / www.jstage.jst.go.jp / article / jscejoe / 71 / 2 / 71_I_1173 / _article / -char / ja / [Non-Patent Document 6] Methodology for "Application of Biochar to Agricultural Land" (Ministry of Agriculture, Forestry and Fisheries, May 2022) https: / / www.maff.go.jp / j / kanbo / kankyo / seisaku / climate / jcredit / biochar / attach / pdf / biochar-2.pdf [Non-Patent Document 7] Calcia Modified Soil Study Group, "Technical Manual (draft) for the Use of Calcia Artificial Stone and Calcia Blocks in Port, Airport, Coastal, and Fisheries Infrastructure Development Works," 2017 [Non-Patent Document 8] Manual for the Use of Low-Carbon Materials in Port Construction, etc. (Ver. 1.0) Kanto Regional Development Bureau, Ministry of Land, Infrastructure, Transport and Tourism (2023) https: / / www.pa.ktr.mlit.go.jp / kyoku / work / CNC / pdf / cnc_manual.pdf [Non-Patent Document 9] Soil preparation and soil diagnosis (12) Characteristics and usage of soil improvement materials - Part 2 - https: / / www.agriweb.jp / column / 1050.html [Non-Patent Document 10] "Directions for Measures Toward the Formation of Carbon Neutral Ports (CNP)" Ministry of Land, Infrastructure, Transport and Tourism (December 2021) https: / / www.mlit.go.jp / kowan / content / 001448303.pdf Summary of the Invention [Problem to be solved by the invention]
[0010] The carbon storage amount of the carbon storage mixed material of the above-mentioned patent application No. 2023-24865 is large, but the mechanical strength is relatively low (uniaxial compressive strength at 28 days is 1.0 N / mm 2 When used in water areas, it is limited to use as a foundation material such as backfilling, shallow water / tidal flat creation, embankment belly / backfilling, etc., and cannot be used with stone or block materials.
[0011] Figure 1 shows examples of the amount of CO2 emitted, absorbed, and fixed, and the balance of CO2 for various conventional materials. The concrete in the figure uses blast-furnace cement type B, and does not contain any added CO2 fixing material (Non-Patent Document 3). The high-fluidity concrete uses calcium carbonate with 313 kg / m2 of fixed CO2 captured from exhaust gas. 3 The environmentally friendly concrete contains 60 kg / m of biochar (Non-Patent Document 4). 3 The artificial calcia stone was added to dredged soil (water content 200%, organic carbon 6.7 kgC / m 3 )648kg / m 3 , blast furnace slag powder 648kg / m 3 , Steelmaking slag 889kg / m 3 It is a blend of the above (Non-Patent Document 5).
[0012] The strength of the environmentally friendly concrete of Non-Patent Document 3 and the high-fluidity concrete mixed with the CO2-immobilized calcium carbonate fine powder of Non-Patent Document 4 is comparable to that of normal additive-free concrete. In addition, as is clear from Figure 1, in the environmentally friendly concrete of Non-Patent Document 3 and the high-fluidity concrete of Non-Patent Document 4, CO2 emissions are reduced by adding a CO2 fixing material, but because a cement material with a high CO2 emission unit is used to achieve strength, the CO2 absorption and storage effect of the concrete material as a whole is small.
[0013] The mechanical strength of the calcia artificial stone blocks is greater than that of calcia-improved soil, and because no cement is used as a solidification material, the CO2 emissions from the materials are lower than those from concrete. However, as shown in Figure 1, from the perspective of carbon storage, only the organic carbon in the dredged soil can be expected, so the CO2 fixation effect is small.
[0014] The ground material in Patent Document 3 contains at least one of cement, ground granular material, blast furnace slag powder, fly ash, silica fume, and rice husk ash, in addition to soft soil and granular material. However, the rice husk ash is not biochar and has no CO2 fixation effect.
[0015] Recently, various initiatives have been introduced to decarbonize port construction, based on the "Direction of Measures Toward the Formation of Carbon Neutral Ports (CNP)" (Non-Patent Document 10). On the other hand, most of the CO2 emissions in port construction are caused by materials such as steel, concrete, and stone, rather than by machine operation or transportation (Non-Patent Document 8). The development and introduction of new technologies that focus on low-carbon and carbon-absorption and -fixation materials that contribute to reducing CO2 emissions in port construction is an urgent task.
[0016] In view of the problems of the prior art as described above, the present invention aims to provide a carbon-storing artificial stone block that utilizes dredged soil and carbon compounds, has a carbon storage effect, and is relatively strong. [Means for solving the problem]
[0017] The carbon-storing artificial stone block for achieving the above-mentioned object is an artificial stone block made by mixing dredged soil with steel slag, a binder, and a carbon compound with a carbon content of at least 10 mass%, and solidifying the mixture. The artificial stone block stably stores the carbon compound and has a material strength of at least 1.0 N / mm2 at 28 days. 2 It is.
[0018] With this carbon storage artificial stone block, the mixture of dredged soil, steel slag, binder, and carbon compounds solidifies, fixing the carbon compounds and allowing them to be stored stably for a long period of time, allowing for the effective use of dredged soil and the production of artificial stone blocks with relatively high strength after 28 days. With a carbon content of at least 10% by mass in the carbon compounds, efficient carbon storage can be achieved.
[0019] In the carbon storage artificial stone block, the binder is preferably at least one of cement, ground granulated blast furnace slag, slaked lime, and fly ash.
[0020] The carbon compound is preferably either an inorganic compound or an organic compound, or a combination of both.
[0021] The inorganic compounds include carbonates such as calcium carbonate and biochar, which contain almost no organic matter that is subject to biodegradation. Under solidification conditions, physical leakage and scattering are suppressed and the compounds are stably retained, allowing the carbon storage effect to be maintained for a long period of time.
[0022] The organic compounds mentioned above include rice husks, rice straw, wood chips, bamboo chips, compost, seaweed, seaweed, and other biological resource materials with a carbon content of about 20 to 50%. When such biological resource materials are used, the high pH and low hydraulic conductivity (low air permeability) of the solidified soil made from dredged soil and steelmaking slag inhibits biodegradation by microorganisms, and the soil is prevented from running off or scattering under the solidified conditions, allowing the soil to be stably retained, thereby maintaining the carbon storage effect over the long term.
[0023] The carbon compound is preferably at least one selected from the group consisting of carbonates, biochar, rice husks, rice straw, wood chips, bamboo chips, compost, seaweed, and seaweed.
[0024] The carbon compound is then mixed with the dredged soil, the steel slag, and the binder in a unit volume (m 3 It is preferable to mix the dredged soil in an amount of 40 to 70 vol % based on the total volume of the dredged soil, the steel slag, and the binder.
[0025] In addition, when the binder is at least one of ground granulated blast furnace slag, blast furnace cement type B, ordinary Portland cement, and fly ash, it is preferable that the amount of binder added is determined so that the strength index calculated by the following formula (1) satisfies the following formula (2). Strength index = (BP + 2×NP + 1.55×BB + 0.35×FA + CH) / W (1) 0.5 ≦ Strength index ≦ 2.5 (2) Where, BP: weight of ground granulated blast furnace slag BB: Weight of blast furnace cement type B NP: weight of ordinary Portland cement FA: weight of fly ash CH: Weight of slaked lime W: weight of water in dredged soil
[0026] The carbon compound is calcium carbonate that is produced by supplying carbon dioxide, an inorganic compound, to the steel slag before the mixing and reacting with the calcium in the steel slag to fix the carbon dioxide, and the calcium carbonate is stably stored in the carbon-storing artificial stone block. That is, the carbon-storing artificial stone block is a material in which steel slag and a binder are mixed with dredged soil, and the steel slag is supplied with carbon dioxide before the mixing and reacts with the calcium in the steel slag to fix the carbon dioxide as calcium carbonate, and the material solidifies into a stone or block shape to stably store the calcium carbonate, and the material has a strength of at least 1.0 N / mm at 28 days. 2 In this case, a carbon compound such as biochar may be mixed, or mixing may be omitted.
[0027] In addition, before the mixing, carbon dioxide, an inorganic compound, is supplied to the steelmaking slag and reacts with the calcium in the steelmaking slag to fix the carbon dioxide as calcium carbonate. This calcium carbonate is then stably stored in the carbon storage artificial stone block together with the mixed carbon compounds.
[0028] The content of the calcium carbonate in the steelmaking slag is preferably within a range of 1 to 20 mass %.
[0029] The carbon storage artificial stone / block is preferably used as any one of rubble, covering stone, backfill stone, fish reef / seaweed reef block, wave dissipating block and covering block.
[0030] The carbon storage artificial stone / block is preferably solid or porous, and if porous, is preferably used for creating seaweed beds and reefs. Effect of the Invention
[0031] According to the present invention, it is possible to provide a carbon-storing artificial stone block that utilizes dredged soil and carbon compounds, has a carbon-storing effect, and is relatively strong. [Brief description of the drawings]
[0032] [Figure 1] 1 is a graph showing examples of CO2 emissions, absorption and fixation amounts, and balance of CO2 for various conventional materials. [Diagram 2] 1A to 1G are schematic diagrams showing examples of use of the carbon storage artificial stone block according to the present embodiment. [Diagram 3] FIG. 1A is a schematic diagram showing an example of using exhaust gas from a plant for pre-mixing CO2 fixation treatment of steelmaking slag in this embodiment, and FIG. 1B is a schematic diagram showing an example of using exhaust gas from a backhoe or a generator. [Figure 4] FIG. 1 is a schematic diagram (a) and (b) showing the elution of compost and compost materials added to a seaweed bed reef constructed from porous carbon-storing artificial stones and blocks according to this embodiment, and a schematic diagram (c) in the case of solid artificial stones and blocks. [Diagram 5] 1 is a graph showing the results of a uniaxial compression test in Experimental Example 1. [Figure 6] 1 is a graph showing the relationship between the amount of carbon compound added and the unconfined compressive strength (σ28) in Experimental Example 2. [Figure 7] 1 is a graph showing the relationship between the amount of carbon compound added and the unconfined compressive strength (σ28) in Experimental Example 3. [Figure 8] 1 is a graph showing the relationship between the amount of carbon compound added and the unconfined compressive strength (σ28) in Experimental Example 4. [Figure 9] 1 is a graph showing the relationship between the amount of carbon compound (inorganic compound) added and the strength ratio for unconfined compressive strength σ7 in Experimental Examples 1, 3, and 4. [Figure 10] 1 is a graph showing the relationship between the amount of carbon compound (inorganic compound) added and the strength ratio for unconfined compressive strength σ28 in Experimental Examples 1, 3, and 4. [Figure 11] 13 is a graph showing the unconfined compressive strength σ28 and the amount of CO2 fixed at 28 days in Experimental Example 5. [Figure 12] 13 is a graph showing the relationship between the strength index and the unconfined compressive strength σ28 in Experimental Example 6. [Figure 13] Photograph (a) shows the state of the granular mixture immediately after mixing and stirring in Experimental Example 6 with a strength index of 0.5, photograph (b) shows the same mixture with a strength index of 1.0, and photograph (c) shows the same mixture with a strength index of 1.5. [Figure 14] 13 is a photograph showing the state of a porous artificial stone block immediately after demolding after 28 days of age in Experimental Example 6. [Figure 15] 13 is a graph showing the unconfined compressive strength σ28 in Experimental Example 7. [Figure 16] 13 is a graph showing the measurement results of the inorganic carbon content of CO2-fixing steelmaking slag and artificial stone mixed with CO2-fixing steelmaking slag in Experimental Example 7. [Figure 17] Photographs of backscattered electron images of untreated steelmaking slag (a) and CO2 fixed steelmaking slag (b) in Experimental Example 7. [Figure 18] 13A and 13B show EDS qualitative analysis charts (spectra 161, 166) of untreated steelmaking slag in Experimental Example 7, and FIG. 13C is an electron beam image showing the target areas of each EDS qualitative analysis. [Figure 19] 13A and 13B are diagrams showing EDS qualitative analysis charts (spectra 175, 183) of the CO2 fixed steelmaking slag in Experimental Example 7, and FIG. 13C is a photograph of an electron beam image showing the target areas of each EDS qualitative analysis. [Figure 20] Photographs of backscattered electron images of untreated steelmaking slag (a) and carbon-storing artificial stone made of CO2-fixing steelmaking slag in Experimental Example 7 (b). [Figure 21] 13A and 13B show EDS qualitative analysis charts (spectra 142, 133) of the artificial stone mixed with untreated steelmaking slag in Experimental Example 7, and FIG. 13C is an electron beam image showing the target areas of each EDS qualitative analysis. [Figure 22] 1A and 1B show EDS qualitative analysis charts (spectra 146, 150) of the carbon-storing artificial stone made of CO2-fixing steelmaking slag in Experimental Example 7, and FIG. 1C is an electron beam image showing the target areas of each EDS qualitative analysis. [Figure 23] FIG. 2 is a schematic diagram for explaining the increase in strength of the carbon-storing artificial stone mixed with CO2-fixing steelmaking slag in this experimental example. [Figure 24] 13 is a graph showing the unconfined compressive strength σ28 of each artificial stone in Experimental Example 8 after 28 days. [Diagram 25] 13 is a graph showing the measurement results of the inorganic carbon content of each artificial stone in Experimental Example 8. [Figure 26] Photographs of secondary electron images (a) and (b) of the carbon-storing artificial stone containing rice husk charcoal in Experimental Example 8, and photographs of backscattered electron images (c) and (d) of the artificial stone. [Figure 27] 1A to 1C show EDS qualitative analysis charts (spectra 6, 1, 3) of the carbon-storing artificial stone with added rice husk charcoal in Experimental Example 8, and FIG. 1D is an electron beam image showing the areas subjected to each EDS qualitative analysis. [Figure 28] 2 is a graph showing an example of the overall CO2 reduction effect of the carbon storage artificial stone block material according to this experimental example, in comparison with the conventional material in FIG. 1. [Figure 29] Photographs (a) to (f) show the state of test specimen culture and wakame zoospores in Experimental Example 9. [Diagram 30] 13A is a diagram showing the measurement surface where the number of seaweed plants and leaf length were measured in Experimental Example 9, and FIG. 13B is a photograph showing the measurement conditions. [Diagram 31] This is a graph showing the average number of seaweed growing individuals from the results of an experiment on carbon-storing artificial stones made from rice husk charcoal, calcium carbonate (CaCO3), and CO2-fixing steel slag in Experimental Example 9, artificial stones without any additives, and the conventional base material concrete. [Diagram 32] 32 is a graph showing the average leaf length of the results of a seaweed growth experiment similar to that of FIG. 31 in Experimental Example 9. [Diagram 33] 13 is a photograph showing an experimental stand equipped with carbon-storing artificial stone blocks for underwater transplantation and growth in Experimental Example 9. [Diagram 34] 13 is a photograph showing the state of the underwater growth experiment in Experimental Example 9. [Diagram 35] 1 is a photograph showing the growth of wakame seaweed as a comparison example of Experimental Example 9 (No. 1 / no addition). [Diagram 36] This is a photograph showing the growth of wakame seaweed when rice husk charcoal from Experimental Example 9 was mixed in (No. 2). [Figure 37] 13 is a photograph showing the growth of wakame seaweed when calcium carbonate was mixed in Experimental Example 9 (No. 3). [Figure 38] 13 is a photograph showing the growth of wakame seaweed when CO2 fixing steelmaking slag was mixed in (No. 4) in Experimental Example 9. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0033] The carbon storage artificial stone block according to the present embodiment is a carbon absorption and fixation type material that contributes to the measures against CO2 emission sources derived from materials by mixing and fixing carbon compounds in the calcia artificial stone block, giving it a carbon storage function of stably storing carbon.
[0034] In other words, carbon storage artificial stone blocks are made by mixing dredged soil with steel slag, and then further mixing it with binders such as cement, ground granulated blast furnace slag, or fly ash, and a carbon compound with a carbon content of at least 10% by mass. The material is then solidified into a stone or block shape, which stably stores the carbon compound and has a compressive strength of at least 1.0 N / mm 2 It has a strength of 28 days and is an alternative material to stone and blocks, with carbon compounds that store carbon and increase the strength of artificial stones and blocks. The mixing in the production of carbon-storing artificial stones and blocks can be done with a mixer, backhoe, drop mixer, etc.
[0035] Carbon compounds can efficiently store carbon if they contain at least 10% by mass of carbon. Specifically, biological resources such as rice husks, rice straw, wood chips, bamboo chips, compost, seaweed, and other materials with a carbon content of 20-50% by mass, biochar with a carbon content of 35-77% by mass, and carbonates such as calcium carbonate can be used. One of these may be used, but multiple types may also be added in combination. The carbon content of calcium carbonate is C / CaCO3=12 / 100=12% by mass, based on the molecular weight.
[0036] Among carbon compounds, biochar and carbonates such as calcium carbonate contain almost no organic matter that is subject to biodegradation and are non-degradable inorganic compounds. Under the solidification conditions of the carbon storage artificial stone / block, physical leakage and scattering are suppressed and the carbon storage effect can be maintained for the long term by being stably retained.
[0037] Furthermore, biological resource materials such as rice husks, rice straw, wood chips, bamboo chips, compost, seaweed, and seaweed are degradable organic compounds, but the high pH and low hydraulic conductivity (low air permeability) of the solidified soil made from dredged soil, steelmaking slag, and binders inhibits biodegradation by microorganisms, and the soil is prevented from running off or scattering under the solidified conditions, allowing the carbon storage effect to be maintained over the long term.
[0038] In the carbon storage artificial stone block according to this embodiment, it is preferable to mix dredged soil with 40 to 70 vol% of the total volume of the dredged soil, steel slag, and binder. The steel slag is mixed as an aggregate. In addition, the carbon compound is mixed with the dredged soil, steel slag, and binder in an amount of 40 to 70 vol% of the total volume of the dredged soil, steel slag, and binder (1 m 3 For example, the organic compound is preferably added in an amount of 10 to 500 kg per unit volume (1 m 3 The amount of the inorganic compound added is preferably 10 to 500 kg per unit weight, more preferably 10 to 450 kg per unit weight, and more preferably 10 to 300 kg per unit weight. The amount of the inorganic compound added is preferably 10 to 500 kg. As the carbon compound, an organic compound and an inorganic compound may be combined, mixed, and solidified.
[0039] In addition, one or at least two of the following may be used as the binder: ground granulated blast furnace slag, blast furnace cement type B, ordinary Portland cement, hydrated lime, and fly ash. The amount of binder to be added is determined so that the strength index calculated by the following formula (1) satisfies the following formula (2). Strength index = (BP + 2×NP + 1.55×BB +0.35×FA + CH) / W (1) 0.5 ≦ Strength index ≦ 2.5 (2) Where, BP: weight of ground granulated blast furnace slag BB: Weight of blast furnace cement type B NP: weight of ordinary Portland cement CH: Weight of slaked lime FA: weight of fly ash W: weight of water in dredged soil
[0040] Steelmaking slag may have carbon dioxide (CO2) fixed as calcium carbonate (CaCO3), and the material mixed with steelmaking slag with CO2 fixation as aggregate may be solidified into a stone or block shape, so that calcium carbonate is stably stored. In this case, the steelmaking slag may be mixed with other carbon compounds and solidified. Such steelmaking slag can be turned into CO2-fixed steelmaking slag by supplying CO2, an inorganic compound, to the slag before mixing with the dredged soil and reacting with the calcium (Ca) in the steelmaking slag.
[0041] The carbon storage artificial stone according to this embodiment can be used for stone materials such as rubble, covering stones, and backfill stones, and the carbon storage block can be used for blocks such as fish reef / seaweed reef blocks, wave dissipating blocks, and covering blocks.
[0042] Specific examples of use of the carbon storage artificial stone / block according to this embodiment will be described with reference to Figs. 2(a)-(g). Fig. 2(a) shows an example in which the artificial stone / block is used as a seaweed bed reef 11, but it may also be used as a fish reef mounting material, and the block is used as a fish reef block 12, 13. Fig. 2(b) shows an example in which the artificial stone / block is used as a breakwater middle filler stone 14, a wave dissipating block 15, and a cover stone 16 for a foundation rubble M installed on the port side of a caisson K such as a quay, and as a middle filler stone 17 and a cover block 18 installed on the port side. Fig. 2(c) shows an example in which the artificial stone is used as a stone material 19 for a submerged earth retaining breakwater constructed on the original ground G at the bottom of the water. Fig. 2(d) shows an example in which the artificial stone is used as a base material 20 and a surface material 21 for a tidal flat on the original ground G. Figures 2(e) and (f) show examples where the artificial stone is used as a partition embankment 22 for landfill construction etc. on original ground G, and as temporary road material 23 on foundation rubble M. Figure 2(g) shows an example where the artificial stone is used as backfill stone 24 and backing material 25 for artificial ground for landfill construction etc. on original ground G. In each of the above examples of use, the carbon compounds fixed by the solidification of the carbon storage artificial stone block can be prevented from flowing out into the water, and in particular when used in the sea, it can be prevented from flowing out into the surrounding sea area due to the influence of waves.
[0043] The carbon storage artificial stone block according to this embodiment is a paste-like material with fluidity obtained by mixing dredged soil, steel slag, carbon compounds, and binders when actually used, but it is solidified into a stone or block shape on land after a predetermined curing period and then thrown and installed at the construction site, or thrown and installed in stone or block form at the construction site and solidified after a predetermined curing period, and functions as the stone or block described above. The carbon storage artificial stone block is in a normal solid form (not porous), but may be porous. The carbon compound is added and mixed in various forms such as the raw material form, chips, powder, flakes, small pieces, and short pieces.
[0044] According to the carbon storage artificial stone block of this embodiment, the mixed material of dredged soil, steel slag, binder, and carbon compound is solidified to fix the carbon compound and store it stably for a long time, so that the carbon compound can be stored stably for a long time, the dredged soil can be effectively used, and an artificial stone block with a relatively high strength after 28 days can be obtained. The carbon content of the carbon compound is at least 10 mass%, so efficient carbon storage can be realized.
[0045] Next, an example of fixing CO2 as calcium carbonate (CaCO3) by supplying exhaust gas containing carbon dioxide (CO2) to steelmaking slag before mixing the steelmaking slag with dredged soil will be described with reference to Figures 3(a) and (b). Figure 3 is a schematic diagram (a) showing an example of using exhaust gas from a plant for CO2 fixation treatment for steelmaking slag before mixing, and a schematic diagram (b) showing an example of using exhaust gas from a backhoe or generator.
[0046] As shown in Fig. 3(a), exhaust gas containing CO2 discharged from the plant PL is supplied to the steelmaking slag SS stored in the steelmaking slag CO2 fixing yard 100 by a CO2 supply device 110 through a CO2 supply pipe 120. Also, as shown in Fig. 3(b), exhaust gas containing CO2 discharged from a backhoe BH or a generator GP is supplied to the steelmaking slag SS stored in the steelmaking slag CO2 fixing yard 100 by the CO2 supply device 110 through a CO2 supply pipe 120. The CO2 supply pipe 120 is preferably composed of a plurality of pipes having a large number of holes, and is installed in advance at the bottom of the steelmaking slag CO2 fixing yard 100, and granular steelmaking slag SS is piled up and stored on it.
[0047] In the steel slag SS shown in Fig. 3(a)(b), CO2 in the exhaust gas is supplied and reacts with calcium (Ca) contained in the steel slag SS, and CO2 is chemically fixed as calcium carbonate (CaCO3) and the like. With such CO2-fixing steel slag, the following two types of carbon storage artificial stone blocks can be obtained. In one, dredged soil is mixed with CO2-fixing steel slag, the binder as described above, and carbon compounds such as biochar, and the mixture is solidified into a stone or block shape after a specified curing period, so that carbon compounds and calcium carbonate are stably stored. In the other, dredged soil is mixed with CO2-fixing steel slag and the binder as described above, and the mixture is solidified into a stone or block shape after a specified curing period, so that calcium carbonate is stably stored. In both of the above carbon storage artificial stone blocks, the CO2 fixation effect can be obtained by chemically fixing CO2 as calcium carbonate (CaCO3) and the like in the steel slag.
[0048] The plants PL in FIG. 3(a) include blast furnaces, converters, thermal power plants, oil refineries, cement plants, asphalt plants, incineration facilities, compost manufacturing plants, etc. The backhoe BH in FIG. 3(b) may be other construction machines, mixer trucks, etc. The type of CO2 gas is not limited to exhaust gas, and CO2 gas captured from exhaust gas of factories and plants by CO2 separation and capture technology (e.g., chemical absorption method, physical adsorption method, etc.), or dry ice may be supplied to steelmaking slag and fixed as CaCO3. The steelmaking slag with carbon dioxide fixed in it may be used as aggregate for carbon storage artificial stone / block, and calcium carbonate is stably stored as a carbon compound.
[0049] Next, the effect of using the porous carbon storage artificial stone / block according to this embodiment in a seaweed bed reef will be described with reference to Figs. 4(a)-(c). When the carbon storage artificial stone / block to which compost / composting material is added as a carbon compound (organic compound) is used to create the seaweed bed reef 11 in Fig. 2(a), the porous structure, as shown in Figs. 4(a) and (b), can provide a seaweed promotion effect due to the elution of the compost / fertilizer material from the inside, and can also provide the effect of facilitating the settlement of seaweed spores and preventing damage caused by sea urchins, snail shells, etc. in the early stages of settlement. That is, it is possible to add a seaweed promotion effect by eluting compost or fertilizer material that promotes seaweed growth from the gaps inside the porous artificial stone / block. In addition, seaweed spores are taken in and easily settled in the eddy current area formed around the micro-topography of the surface, and the effect of suppressing initial attrition due to the prevention of damage caused by seaweed in the early stages of settlement (sea urchins, snail shells, etc.) can be expected. Furthermore, if the artificial stones / blocks are in a normal solid form, the effect of preventing the leaching of compost / compost materials will decrease, as shown in Figure 4(c).
[0050] Table 1 below shows an example of the composition of the carbon storage artificial stone block according to this embodiment.
[0051] [Table 1]
[0052] In Table 1, when the strength index of ground granulated blast furnace slag is 1.0 according to the above formula (1), the unit volume (m 3 ) is 408 kg. Carbon compounds (biochar, calcium carbonate) are added as an extra percentage. The amount of CO2 fixed (kg-CO2) was calculated by the formula: amount of carbon compound (kg-dry) x carbon content (%) x 44 / 12. The carbon content of the carbon compounds was set to 77 mass% for biochar and 12 mass% for calcium carbonate. For the CO2 fixed steelmaking slag, the amount of CO2 fixed was calculated as the amount when steelmaking slag was exposed to exhaust gas with a CO2 concentration of 20% for 3 hours.
[0053] Dredged soil contains about 1.5% carbon (equivalent to 24 kg-CO2 / m 3However, as in the compounding examples in Table 1, it can be seen that the material according to this embodiment can store several times this amount of carbon by adding a carbon compound.
[0054] (Experimental Example) Next, an experimental example of the present invention will be described. Note that the present invention is not limited to the carbon storage artificial stone block of this experimental example.
[0055] Experimental Example 1 As shown in Table 2 below, dredged soil (water content 163.3%, liquid limit 65.3%) with a mixing ratio of 50 vol% and steel slag (surface dry density 2.85 g / cm 3 ) and ground granulated blast furnace slag (density 2.89g / cm 3 Case 1 (no carbon compound added) was a material (conditions etc. the same as in Table 1) mixed with rice husk charcoal (biochar) as a carbon compound, Case 2 was a material to which calcium carbonate was added, and Case 3 was a material to which CO2 was added. Furthermore, Case 4 was a material in which the steelmaking slag in Case 1 was replaced with steelmaking slag that had fixed CO2. The carbon compounds in Cases 2 and 3 fixed an additional CO2 of 87 kg-CO2 / m 3 To match, the outer ratio is 32kg / m 3 , 197kg / m 3 The CO2 fixed steelmaking slag in Case 4 was produced by blowing and exposing exhaust gas (CO2 concentration: approximately 18%) from a small internal combustion generator into a sealed bag containing steelmaking slag before mixing for 3 hours. This production method utilizes a chemical reaction in which CaO, which is abundant in steelmaking slag, reacts with CO2 in the exhaust gas to produce CaCO3. The CaO content of the steelmaking slag used in the experiment was 43.4% (free lime 8.4%). The amount of steelmaking slag mixed was 1,073 kg / m 3 On the other hand, the amount of calcium carbonate fixed by the above ventilation and exposure was 7.3% (78 kg / m 3 ) and the amount of CO2 fixed in the CO2-fixing steelmaking slag is 34 kg-CO2 / m 3Artificial stones were produced using each of the materials in cases 1 to 4, and uniaxial compression tests (JIS A1216:2020) were conducted after 7 days of curing and after 28 days of curing.
[0056] [Table 2]
[0057] The results of the unconfined compression test are shown in Table 2 and Figure 5. The unconfined compression strength (σ28) at 28 days (after 28 days of curing) was 1.0 N / mm for all cases 2 to 4. 2 Comparing the unconfined compressive strength σ28 at 28 days, cases 2 and 3, where rice husk charcoal (biochar) and calcium carbonate were added, showed 38% and 21% increased strength, respectively, compared to case 1, where no carbon compound was added. Also, a 9% increase in strength was confirmed in case 4, where steelmaking slag was replaced with CO2-fixing steelmaking slag.
[0058] Experimental Example 2 (organic compound) As shown in Table 3 below, dredged soil (water content 163.5%, liquid limit 65.4%) with a mixing ratio of 50 vol% and steel slag (surface dry density 3.01 g / cm 3 ), ground granulated blast furnace slag (density 2.89g / cm 3 Artificial stones and blocks were made by adding carbon compounds to a material mixed with cellulose (carbonaceous materials, strength index 1.00), and uniaxial compression tests (JIS A1216:2020) and table flow tests (JIS R 5201:2015) were conducted on the 7th and 28th days of age. Organic compounds such as rice husks, compost, and seaweed (raw seaweed), as well as inorganic compounds such as rice husk charcoal, were added and mixed in the amounts shown in Table 3 (outside ratios). Seaweed (raw wakame) was cut to approximately 5mm x 5mm in consideration of the specimen size (Φ5 x 10cm) for the compression test. Rice husk charcoal is a representative of various biochars, rice husks are representative of rice husks, rice straw, wood chips, bamboo chips, etc., compost is a representative of organic compost (produced at the Miki Composting Center), and raw seaweed is a representative of seaweed and seaweed.
[0059] [Table 3]
[0060] The amount of CO2 fixed in Table 3 was calculated using the following formula. Amount of CO2 fixed = amount of carbon compound added (kg / m 3 ) × Carbon content (%) × 44 / 12 (← CO2 / C) The amount of CO2 fixation was added by adding carbon compounds, and the amount of CO2 fixation in the material made by mixing dredged soil, steel slag, and binder is not included. The following carbon contents were used to calculate the amount of CO2 fixed: Rice husk charcoal 77% (Non-patent document 6) Rice husk 40% (Non-patent Document 9) Compost 17% (Analysis report, January 31, 2023, Institute of Environmental Biochemistry) Seaweed (raw Ulva) 38% (actual value: CNS elemental analyzer) Moisture content: 90% (Actual value: Moisture analyzer)
[0061] The experimental results of Experimental Example 2 (unconfined compressive strength σ7, σ28, and table flow value at ages of 7 and 28 days) are shown in Table 3 and Figure 6 (unconfined compressive strength σ28). In all cases (No. 6 to 17), the unconfined compressive strength was 1.0 N / mm 2 The above unconfined compressive strengths σ7 and σ28 were obtained. In addition, in cases 15 to 17, most of the water in the added amount of Ulva has a hydrating effect, and the table flow value is high, so that appropriate workability can be ensured if an appropriate amount is used. Furthermore, limiting the amount of water added to the dredged soil contributes to the effective use of the dredged soil. On the other hand, since the carbon content is based on the carbon in the dried sample, the net carbon storage amount is relatively low. Rice husks, etc. may also be dried in the same way and used.
[0062] Experimental Example 3 (Inorganic compound) As shown in Table 4, artificial stone blocks were manufactured by adding carbon compounds to a mixture of dredged soil, steel slag, and ground granulated blast furnace slag under the same conditions as in Experimental Example 2, and artificial stone blocks were manufactured by replacing the steel slag with CO2 fixing slag. Uniaxial compression tests (JIS A1216:2020) and table flow tests (JIS R 5201:2015) were carried out on the 7th and 28th days of material age. The carbon compound was calcium carbonate, an inorganic compound, and was added and mixed in the amounts shown in Table 4. The CO2 fixing steel slag was prepared in advance before mixing by placing a tray with steel slag evenly spread to a thickness of about 5 mm in a CO2 incubator and curing it for an arbitrary time under conditions of CO2 concentration 20%, temperature 25°C, and humidity 80%. This method uses a chemical reaction that generates CaCO3 by reacting CaO in steel slag with CO2 in the incubator, using the same principle as in Experimental Example 1. Steelmaking slag used in this experiment: Same CaO content and free lime as in Experimental Example 1 The relationship between the amount of additional CaCO3 fixed (content) by the CO2 reaction, the curing time, and the CO2 concentration is as follows. Additional fixed amount Curing time CO2 concentration CaCO3+2.5% 15 minutes 20% CaCO3+5.0% 23 minutes 20% CaCO3+7.5% 360 minutes 20%
[0063] [Table 4]
[0064] The amount of CO2 fixed was calculated using the following formula. (1) Calcium carbonate CO2 fixed amount = added amount (kg / m 3 ) ×44 / 100 (← CO2 / CaCO3) (2) CO2 fixed steelmaking slag Amount of CO2 fixed = CaCO3 additional fixation rate (%) x steel slag mixture amount (1075 kg) × 44 / 100 (← CO2 / CaCO3)
[0065] The experimental results of Experimental Example 3 (unconfined compressive strength σ7, σ28, and table flow value at ages of 7 and 28 days) are shown in Table 4 and Figure 7 (unconfined compressive strength σ28). In all cases (No. 19 to 24), the unconfined compressive strength was 1.0 N / mm 2 The unconfined compressive strengths σ7 and σ28 above were obtained. In the cases of No. 19 to 21, although there was some variation, it was confirmed that the strength was maintained or slightly increased when the amount of carbon compound added was in the range of 27 to 108 kg. In the cases of No. 23 and 24, the table flow value was 100 mm, which was a significant decrease in fluidity, and it was considered difficult to significantly increase the amount added any further. Looking at No. 18 to 24 overall in terms of the amount of carbon compound added, the average strength was 150 kg / m 3 It was considered that there was a tendency for the strength of the convex function to increase with a maximum near the
[0066] Experimental Example 4 (Inorganic compound) As shown in Table 5 below, a material was prepared by mixing dredged soil, steelmaking slag with pre-fixed CO2, and ground granulated blast furnace slag under the same conditions as in Experimental Example 3, and a uniaxial compression test (JIS A1216:2020) and a table flow test (JIS R 5201:2015) were conducted on the 7th and 28th days of the material age. The materials used, the CO2 fixation method, and the method for calculating the amount of CO2 fixation were the same as in Experimental Example 3. The relationship between the amount of additional CaCO3 fixed (content), curing time, and CO2 concentration is as follows. Additional fixed amount Curing time CO2 concentration CaCO3+5.0% 12 min 100% CaCO3+10.0% 100min 100% CaCO3+15.0% 900min 100%
[0067] [Table 5]
[0068] The experimental results of Experimental Example 4 (unconfined compressive strengths σ7, σ28, and table flow values at ages of 7 and 28 days) are shown in Table 5 and Figure 8 (unconfined compressive strength σ28). In all cases (Cases 26 to 28), the unconfined compressive strength was 1.0 N / mm 2The unconfined compressive strength σ28 was obtained. The amount of calcium carbonate added was 50-100kg / m 3 A tendency for the strength of the convex function to increase with a maximum near the
[0069] Next, we will explain the relationship between the amount of inorganic compound added and the strength of the artificial stone block in this experimental example. Figures 9 and 10 show the strengths σ7 and σ28 of the artificial stone block to which the inorganic carbon compound was added, obtained in experimental examples 1, 3, and 4, compared with the strength at 0 kg / m 3 8 and 9 are graphs showing the relationship between the intensity ratio of intensities σ7 and σ28 in the case of 0 kg / m2 and the amount of added carbon compound. 3 ), and the dashed line is the 20% value of the coefficient of variation (CV) of all data. 3 Although there is some variation, there is a tendency for strength to be maintained or increased within the range of 200kg / m 3 The above shows a downward trend.
[0070] Experimental Example 5 (Combination of carbon compounds) As shown in Table 6 below, artificial stones and blocks were made by adding carbon compounds to a mixture of dredged soil, steel slag with pre-fixed CO2, and ground granulated blast furnace slag under the same conditions as in Experimental Example 4, and a uniaxial compression test (JIS A1216:2020) was conducted on the material after 28 days. The carbon compounds were inorganic compounds such as rice husk charcoal and calcium carbonate, and were added and mixed in the amounts (outside ratios) shown in Table 6. The production conditions for steelmaking slag with pre-fixed CO2 are as follows: Additional fixed amount Curing time CO2 concentration CaCO3+2.5% 15 minutes 20%
[0071] [Table 6]
[0072] The experimental results of Experimental Example 5 (unconfined compressive strength σ28 at 28 days) and the amount of CO2 fixed are shown in Table 6 and Figure 11. In all cases (Cases 29 to 32), the CO2 fixation amount was 1.0 N / mm2 The above unconfined compressive strength σ28 was obtained. As shown in Figure 11, it was confirmed that the strength of the artificial stone blocks produced by adding each carbon compound to CO2 fixing steelmaking slag was equal to or slightly increased compared to the case where the same carbon compound was added to untreated steelmaking slag. Even if there are constraints on the raw materials of the carbon compounds or the source of the fixed CO2 (exhaust gas, etc.), it is possible to ensure the carbon storage effect by using different types of carbon compounds.
[0073] Experimental Example 6 (Porous) As shown in Table 7 below, dredged soil with a mixing ratio of 50 vol% (liquid limit wL 65.4%) was compared with steelmaking slag (surface dry density 3.01 g / cm3) in which CO2 had been fixed in advance as in Experimental Example 3, by changing the water content from Wn 163.5% (2.5wL) to Wn 130.6% (2.0wL) to reduce the water content. 3 ) and ground granulated blast furnace slag (density 2.89 g / cm 3 ) and mixed and stirred to produce a granular mixture. Three strength indices were set: 0.5, 1.0, and 1.5. The above granular mixture was packed in a formwork for uniaxial compression tests (Φ5×10cm) in a loosely packed state, cured in a sealed state, and the mixture particles were bonded and solidified to produce a porous artificial stone block. An uniaxial compression test (JIS A1216:2020) was then conducted at a material age of 28 days. The relative water content Wn / wL (for example, 2.5wL and 2.0wL above) between the water content (natural water content) Wn and the liquid limit wL is an index that indicates the hardness and softness of the soil.
[0074] [Table 7]
[0075] In Experimental Example 6, the CO2 fixation method and the calculation method of the amount of fixed CO2 were the same as in Experimental Example 3. The relationship between the amount of additional fixed CaCO3 (content), the curing time, and the CO2 concentration is as follows. Additional fixed amount Curing time CO2 concentration CaCO3+5.0% 12 min 100%
[0076] [Table 8]
[0077] The experimental results of Experimental Example 6 (unconfined compressive strength σ28 at 28 days) are shown in Table 8 and Figure 12. Also, photographs of the appearance of the granular mixture (strength index 0.5, 1.0, 1.5) immediately after mixing and stirring are shown in Figures 13(a)-(c). Also, a photograph of the appearance of the porous artificial stone block immediately after demolding after 28 days is shown in Figure 14. From Table 8 and Figure 12, it was confirmed that the unconfined compressive strength σ28 at 28 days for the porous artificial stone block of Experimental Example 6 increased or decreased depending on the strength index. When manufacturing carbon-storing artificial stone blocks as porous materials, it is also necessary that σ28 is at least 1.0 N / mm 2 It is preferable to set the strength index and mix the composition so that the strength index is set to the value given below.
[0078] Experimental Example 7 (SEM observation of carbon-storing artificial stone made from CO2-fixing steel slag) Carbon-retaining artificial stone was strengthened by adding an appropriate amount of dredged soil to dredged soil, which reacted with the Ca in the steelmaking slag by supplying CO2 to the steelmaking slag to fix it as calcium carbonate, and was observed with a scanning electron microscope (SEM) and energy dispersive X-ray analysis (EDS) to confirm the mineral composition and crystal structure under those conditions. The materials used and the mix conditions of the specimens observed are as follows:
[0079] The artificial stone and block specimens were made by mixing dredged soil, steel slag, and blast furnace slag powder under the same conditions as in Experimental Example 3. The steel slag was untreated and CO2 fixed, and the artificial stone was mixed with untreated steel slag, and the carbon-storing artificial stone was mixed with CO2-fixed steel slag. The steel slag used had the same CaO content and free lime as in Experimental Example 1, and the CO2 supply conditions for CO2 fixation were CO2 concentration 20%, temperature 25 °C, and supply time 23 minutes. The uniaxial compression test and inorganic carbon content measurement were carried out on the 28th day of material age. The inorganic carbon content was measured by adopting the TC-TOC method in accordance with Bottom Sediment Survey Method II-4.2, and the measuring device was a CNS elemental analyzer (CNS928: LECO). Samples were also taken from the specimens in the above strength tests and used as observation objects, and an SEM-EDS SU5000 (Hitachi High-Tech) was used as the observation device.
[0080] Figure 15 shows the unconfined compressive strength σ28 at 28 days, which is the strength of the test specimen obtained in Experimental Example 7. Note that the numbers in Figure 15 indicate average values, and the vertical lines indicate the upper and lower limits of the data (the same applies to Figures 16, 24, 25, 32, and 33 described below). Two specimens were used in the compressive strength test, and the unconfined compressive strength σ28 of the artificial stone mixed with untreated (no CO2 fixation) steelmaking slag was 9,472 kN / m 2 , 9,404kN / m 2 The unconfined compressive strength σ28 of the artificial stone mixed with CO2-fixed steelmaking slag is 11,447 kN / m 2 , 10,250kN / m 2The carbon-storing artificial stone mixed with CO2-fixing steelmaking slag showed a 15% increase in strength in average values compared to untreated (no CO2 fixation) artificial stone mixed with steelmaking slag, and an 8% increase in strength was confirmed when comparing the lower limit of the uniaxial compressive strength σ28 in the case of CO2 fixation with the upper limit of the uniaxial compressive strength σ28 in the case of no CO2 fixation. The strength increase due to moderate CO2 fixation in steelmaking slag was also confirmed in this test specimen. Figure 16 shows the measurement results of the inorganic carbon content of the test specimens (CO2-fixing steelmaking slag, artificial stone mixed with CO2-fixing steelmaking slag). In the CO2-fixing steelmaking slag in which CO2 was supplied to the steelmaking slag, an increase in inorganic carbon content of +0.8%-C (6.5%-CaCO3) was confirmed. In the artificial stone mixed with CO2-fixing steelmaking slag, an increase in inorganic carbon content of +0.5%-C (3.8%-CaCO3) was also confirmed.
[0081] The results of SEM-EDS observation of the above test specimens are explained. Figure 17 shows the backscattered electron images of untreated steelmaking slag (a) and CO2 fixed steelmaking slag (b). Figure 18 shows EDS qualitative analysis charts (a) and (b) of spectra 161 and 166 shown in the electron beam image (c) of untreated steelmaking slag. Figure 19 shows EDS qualitative analysis charts (a) and (b) of spectra 175 and 183 shown in the electron beam image (c) of CO2 fixed steelmaking slag. Figure 20 shows the backscattered electron images of artificial stone mixed with untreated steelmaking slag (a) and carbon storage artificial stone mixed with CO2 fixed steelmaking slag (b). Figure 21 shows EDS qualitative analysis charts (a) and (b) of spectra 142 and 133 shown in the electron beam image (c) of artificial stone mixed with untreated steelmaking slag. Figure 22 shows EDS qualitative analysis charts (a) and (b) of spectra 146 and 150 shown in the electron beam image (c) of carbon-storing artificial stone mixed with CO2-fixing steelmaking slag.
[0082] As shown in Figure 17(a)(b), Figure 18(a)(b), and Figure 19(a)(b), the backscattered electron images and EDS qualitative analysis charts of untreated steelmaking slag and CO2 fixed steelmaking slag confirmed that small crystal pieces of calcium carbonate were formed on the surface of the CO2 fixed steelmaking slag. This is thought to be due to the following reactions (1) and (2) that are used by carbon storage artificial stones to fix inorganic carbon compounds. (1) Hydration reaction of Ca components in steelmaking slag "CaO + H2O → Ca(OH)2" (spontaneous reaction) (2) Carbonation reaction by supplying CO2: Ca(OH)2+ CO2 → CaCO3+ H2O
[0083] As shown in Figures 20(a)(b), 21(a)(b), and 22(a)(b), the artificial stone mixed with untreated steelmaking slag had a mineral composition mainly consisting of Friedel's salt, ettringite, and cement hydrates such as CSH. On the other hand, the carbon-storing artificial stone made with CO2-fixing steelmaking slag contained hydrates such as CSH and calcium carbonate, and the surface mineral form of CSH was different from that of the artificial stone mixed with untreated steelmaking slag, and did not have needle-shaped crystals, suggesting the possibility of alteration of cement hydrates due to carbonation. From the above, as shown in the schematic diagram of strength increase in Figure 23, it is suggested that the crystals of calcium carbonate derived from steelmaking slag with moderate CO2 fixation contributed to the densification of the structure of the carbon-storing artificial stone made with CO2-fixing steelmaking slag, and that the slag surface and calcium carbonate pieces separated from the surface acted as nuclei that served as footholds for the cement hydration reaction, contributing to the increase in strength.
[0084] Experimental Example 8 (SEM observation of carbon-retaining artificial stone made from rice husk charcoal) Artificial stone / block specimens were used, made by mixing dredged soil, steel slag, and ground granulated blast furnace slag under the same conditions as in Experimental Example 2. Uniaxial compression tests and inorganic carbon content measurements were carried out at 28 days of age for two cases, one with no additives and one with 50 kg / m3 of rice husk charcoal added in an external ratio. The inorganic carbon content measurements were carried out in the same manner as in Experimental Example 7, and samples were taken from the specimens used in the strength tests described above and used as the observation subject, using the same observation equipment as in Experimental Example 7.
[0085] Figure 24 shows the unconfined compressive strength σ28 at 28 days. Comparing the cases of no additive and those with rice husk charcoal added, the strength was about the same. Figure 25 shows the measurement results of inorganic carbon content. It was confirmed that the carbon content increased with the addition of rice husk charcoal.
[0086] Figures 26(a)(b) show secondary electron images, and Figures 26(c)(d) show backscattered electron images. Figures 27(a)-(c) show EDS qualitative analysis charts of the electron beam image spectra 6, 1, and 3 shown in Figure 27(d). The particularly dark areas in the backscattered electron images of Figures 26(c)(d) indicate the presence of high concentrations of carbon compounds, and the fine shapes and void cells characteristic of plants in the secondary electron images of Figures 26(c)(d) confirmed that the added rice husk charcoal remained in the artificial stone matrix. In the backscattered electron image of region a in Figure 26(d), the surface layer of the rice husk charcoal was different from the dark areas inside, and appeared pale and bright, similar to the artificial stone matrix. In addition, the EDS qualitative analysis results of Figures 27(a)(b) showed the same Ca and Si intensities as the artificial stone matrix. From the above results, it is possible that pastes containing Ca and Si components derived from the artificial stone matrix are seeping into the voids on the surface of the rice husk charcoal, causing hydration and solidification to proceed in an integrated manner, which is thought to contribute to the insolubilization and retention of added carbon compounds.
[0087] Table 9 and Figure 28 show examples of the overall CO2 reduction effect of the carbon storage artificial stone material in Experimental Example 1 (Cases 2 and 4), in comparison with the conventional material in Figure 1. Table 9 and Figure 28 show that the method of mixing and fixing carbon compounds such as biochar into the calcia artificial stone (Case 2), the method of replacing steelmaking slag with CO2 fixing steelmaking slag (Case 4), and the method of mixing and fixing carbon compounds such as biochar and replacing steelmaking slag with CO2 fixing steelmaking slag can add a strength increase effect and contribute to several times more carbon negativity compared to conventional materials.
[0088] [Table 9]
[0089] Experimental Example 9 (Experiment on seaweed growth on carbon storage artificial stone blocks) Figures 29(a)-(f) are photographs showing the wakame zoospores and the test specimen culture conditions in the seaweed adhesion experiment of this experimental example. As shown in Table 10 below, the test specimens of each carbon-storing artificial stone / block with the same mix conditions as in Experimental Example 1 were allowed to have wakame zoospores attached to them and cultured in an indoor water tank. When the maturation of the zoospores to gametophytes and young leaves was confirmed, they were transplanted into the sea and grown as shown in Figures 33 and 34. In addition, a test specimen of unreinforced concrete using blast furnace type B cement was added as a representative conventional base material (block). In other words, each ace was mixed on February 27 and 28, 2023, and a test specimen for wakame adhesion (Φ5×10cm: using a formwork for compression tests) was produced. The test specimens were sealed and cured at 20°C until the material age of 28 days. The test specimens were cured in aerated freshwater from the 29th day to the 59th day of the material age, and it was confirmed that the pH of the immersion freshwater was constant at 8.0 or less. On April 27, 2023, the above-mentioned cured test specimens were immersed in seawater in which fresh wakame spores (mekabu) on the second day of collection were soaked and zoospores were released as shown in Figure 29(b) as shown in Figure 29(a), and the test specimens after the above-mentioned curing were immersed in seawater to allow the zoospores to attach as shown in Figure 29(c). The test specimens on which the zoospores attached were immediately placed quietly in a 100L aquarium tank indoors as shown in Figure 29(d), and the seawater temperature, illuminance, and water quality were controlled to allow them to enter a dormant state (summer dormancy). After that, from October 27, 2023, the temperature and illuminance were gradually changed to mature conditions to allow the spores to grow into young leaves. On November 29, 2023, each test specimen with young wakame leaves attached was transplanted into the sea at a constant depth of 1.0 m as shown in Figures 29(e) and (f) (see Figures 33 and 34). Figures 35 to 38 are photographs showing the growth of wakame in each test specimen taken on December 18 and 19, 2023 after transplantation in the sea. On the same day, the number of attached wakame individuals and leaf length (length of leaf + stem) were measured as shown in Figures 30(a) and (b). The area of the surface for measuring the number of attached individuals and leaf length in Figure 30(a) was 19.6 cm2. 2 It is.
[0090] [Table 10]
[0091] As shown in Figure 31, the average number of algae that grew in the seaweed settlement experiments for the carbon-storing artificial stone / block cases mixed with rice husk charcoal, calcium carbonate (CaCO3), and CO2-fixing steel slag tended to be equal to or higher than artificial stone without any additives. In addition, the four artificial stone cases tended to be higher than the conventional base material of concrete. As shown in Figure 32, the average leaf length was about the same for the four artificial stone cases, with concrete showing a tendency to be slightly lower than the artificial stone. These results suggest that the settlement and growth of seaweed such as wakame on the carbon-storing artificial stone / blocks shows a tendency to improve compared to conventional concrete base materials.
[0092] Although the embodiment and examples for carrying out the present invention have been described above, the present invention is not limited to these, and various modifications are possible within the scope of the technical concept of the present invention. For example, the carbon storage artificial stone block according to this embodiment is used in water areas and ocean areas in Fig. 2 (a) to (g), but the present invention is not limited to this, and can be used on land as well, and the carbon compounds stably stored in the carbon storage artificial stone block can be prevented from scattering into the atmosphere. [Industrial Applicability]
[0093] According to the present invention, it is possible to manufacture and provide carbon-storing artificial stone / blocks that have a carbon storage effect and are relatively strong, by utilizing dredged soil, carbon compounds, and CO2 fixing steelmaking slag. This not only realizes efficient and stable carbon storage over the long term, but also allows the use of the artificial stone / blocks as substitute materials for rubble, covering stone, backfill stone, fish reef / algae reef blocks, wave-dissipating blocks, or covering blocks. [Explanation of symbols]
[0094] 11 Seagrass reef 12,13 Fish reef block 14 Breakwater Filling Stone 15 Wave-dissipating blocks 16 Covering stone 17 Middle Stone 18 Cladding Blocks 19 Stone materials for earth retaining breakwaters 20 Tidal flats base material 21 Tidal flat surface material 22 Partition embankment 23 Temporary road materials 24 Backfill stone 25 Backside
Claims
1. An artificial stone / block made by mixing dredged soil with steel slag, a binder, and a carbon compound having a carbon content of at least 10% by mass, and solidifying the mixture, The carbon compound is stably stored and has a strength of at least 1.0 N / mm 2 Carbon storage artificial stone blocks.
2. 2. The carbon storage artificial stone / block according to claim 1, wherein the binder is at least one of cement, ground granulated blast furnace slag, slaked lime, and fly ash.
3. 2. The carbon storage artificial stone / block according to claim 1, wherein the carbon compound is either an inorganic compound or an organic compound, or a combination of both.
4. 2. The carbon storage artificial stone / block according to claim 1, wherein the carbon compound is at least one selected from the group consisting of carbonates, biochar, rice husks, rice straw, wood chips, bamboo chips, compost, seaweed and seaweed.
5. The carbon compound was mixed with the dredged soil, the steel slag, and the binder at a unit volume (m 3 2. The carbon storage artificial stone / block according to claim 1, wherein the carbon storage artificial stone / block is mixed in an amount within a range of 10 to 500 kg per 1000 kg of the raw material.
6. 2. The carbon storage artificial stone / block according to claim 1, wherein the dredged soil is mixed at 40 to 70 vol.% of the total volume of the dredged soil, the steel slag, and the binder.
7. 2. The carbon storage artificial stone / block according to claim 1, wherein when the binder is at least one of ground granulated blast furnace slag, blast furnace cement type B, ordinary Portland cement, hydrated lime, and fly ash, the amount of the binder added is determined so that the strength index calculated by the following formula (1) satisfies the following formula (2). Strength index = (BP + 2×NP + 1.55×BB + 0.35×FA + CH) / W (1) 0.5 ≦ Strength index ≦ 2.5 (2) Where, BP: weight of ground granulated blast furnace slag BB: Weight of blast furnace cement type B NP: weight of ordinary Portland cement CH: Weight of slaked lime FA: fly ash weight W: weight of water in dredged soil
8. 2. The carbon storage artificial stone / block according to claim 1, wherein the carbon compound is calcium carbonate in which carbon dioxide, an inorganic compound, is fixed by reacting with calcium in the steelmaking slag.
9. 2. The carbon-storing artificial stone / block according to claim 1, wherein carbon dioxide, an inorganic compound, is fixed as calcium carbonate by reacting with calcium in the steelmaking slag.
10. The carbon-retaining artificial stone / block according to claim 8 or 9, wherein the content of the calcium carbonate in the steelmaking slag is within a range of 1 to 20 mass %.
11. 2. The carbon storage artificial stone / block according to claim 1, which is used for any one of rubble, covering stone, backfill stone, fish reef / seaweed reef block, wave dissipating block and covering block.
12. 12. The carbon storage artificial stone / block according to claim 1 or 11, which is in a solid or porous form.
13. 2. The carbon storage artificial stone or block according to claim 1, which is porous and is used for creating seaweed beds and reefs.
Citation Information
Patent Citations
Mud reforming material and method
JP2009121167A
Method for producing artificial stone
JP2012148948A
Ground material and ground improvement method
JP2018184823A
JP2023224868A